Fecal microbiota transplantation confirmed that 919 Syrup reduced the ratio of erucamide to 5-AVAB in hippocampus to alleviate postpartum depression by regulating gut microbes - Zheng, Qiaoqi; Wang, Shusheng; Tian, Xinyun; Liu, Wen; Gao, Pengfei (Frontiers in Immunology, 2023)
Background Postpartum depression has a crucial impact on the physical and psychological comfort and the work of postnatal women, the growth and development of infants and mental health in adulthood. Finding a safe and effective anti-postnatal depression drug is currently an important research goal in this field. Methods In this study, the forced swimming test (FST) and tail suspension test (TST) were used to evaluated the depressive behaviors of mice, and the changes of metabolites and intestinal microflora in mice with postpartum depression were examined through non-target metabolomics and 16S RNA sequencing respectively. Results We found that traditional Chinese medicine compound 919 Syrup could alleviate postpartum depression in mice and inhibit the elevated erucamide level in depressive hippocampus. However, mice treated with antibiotics were not sensitive to the anti-postnatal depression effect of 919 Syrup, and the level of 5-aminovaleric acid betaine (5-AVAB) in their hippocampus was significantly decreased. Transplanting fecal microflora treated with 919 Syrup could effectively improve the depressive behaviors of mice, upregulate the level of gut-derived 5-AVAB in the hippocampus, and downregulate the level of erucamide. Erucamide was significantly negatively correlated with increased Bacteroides in intestine after 919 Syrup treatment or fecal transplantation, and significantly positively correlated with Ruminococcaceae UCG-014 which was increased in feces of mice with postpartum depression. The increase of Bacteroides, Lactobacillus, and Ruminiclostridium in intestine after fecal transplantation had a clearly positive correlation with 5-AVAB. Conclusion In brief, 919 Syrup may downregulate the ratio of hippocampal metabolites erucamide to 5-AVAB by regulating intestinal flora to alleviate postpartum depression, laying a scientific foundation for future pathological research and development of therapeutic drugs for postpartum depression.